MANAJEMEN PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS (ABK) - Hernani Hernani; Sowiyah Sowiyah; Sumadi Sumadi (Program Studi Magister Manajemen Pendidikan)
The purpose of this study was to analyze the implementation of Education Management Children with Special Needs in SMPN 9 and SMPN 10 Metro City, included: 1) Planning of education, 2) Implementation of education, 3) Evaluation of education, 4) factors supporting and education management. This study used a qualitative approach with a multi-site study design. Data was collected by interview, observation, and documentation. The Research Result of education management children with special needs education management have been run in accordance with the applicable regulations is the curriculum that is used together with other regular school. Teachers who teach in the classroom inclusion makes learning program design according to the characteristics and needs of each learner. Factors supporting the implementation of education children with special needs received financial assistance from the central government, teachers consistently carried out its duties and functions, there is also adequate learning media, communicated with parents is good enough.Tujuan penelitian ini untuk menganalisis implementasi Manajemen Pendidikan Anak Berkebutuhan Khusus (ABK) di SMPN 9 dan SMPN 10 Metro, meliputi: 1) Perencanaan pendidikan, 2) Pelaksanaan pendidikan, 3) Evaluasi pendidikan, 4) Faktor-faktor pendukung dan penghambat manajemen pendidikan ABK. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi multi situs. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi, dan dokumentasi. Hasil penelitian manajemen pendidikan ABK ini sudah berjalan sesuai dengan peraturan yang berlaku yaitu kurikulum yang digunakan sama dengan sekolah reguler lainnya. Guru yang mengajar di kelas inklusi membuat rancangan program pembelajaran yang sesuai dengan karakteristik dan kebutuhan setiap peserta didik. Faktor pendukung pelaksanaan pendidikan ABK mendapat bantuan dana dari pemerintah pusat, guru-guru konsisten melaksanakan tugas dan fungsinya, tersedia juga media belajar yang memadai, komunikasi dengan orang tua cukup baik.Kata kunci: anak berkebutuhan khusus, manajemen pendidikan, sekolah menengah pertama